Calcium Permeable-AMPA Receptors and Excitotoxicity in Neurological Disorders - Guo, Changyong; Ma, Yao-Ying (Frontiers in Neural Circuits, 2021)
Excitotoxicity has been identified as one of the primary mechanisms of cell loss in a variety of diseases of the central and peripheral nervous systems. Other than the previously established signaling pathways of excitotoxicity, which depend on the excessive release of glutamate from axon terminals or over-activation of NMDA receptors (NMDARs), Ca2+ influx-triggered excitotoxicity through Ca2+-permeable (CP)-AMPA receptors (AMPARs) has been detected in multiple disease models. In this review, both acute brain insults (e.g., brain trauma or spinal cord injury, ischemia) and chronic neurological disorders, including Epilepsy/Seizures, Huntington’s disease, Parkinson’s disease, Alzheimer’s disease, amyotrophic lateral sclerosis, chronic pain, and glaucoma, are discussed regarding the CP-AMPAR-mediated excitotoxicity. Considering the low expression or absence of CP-AMPARs in most cells, specific manipulation of the CP-AMPARs might be a more plausible strategy to delay the onset and progression of pathological alterations with fewer side effects than NMDARs.